Selective binding and lateral clustering of α5β1 and αvβ3 integrins: unraveling the spatial requirements for cell spreading and focal adhesion assembly - Schaufler, Viktoria; Czichos-Medda, Helmi; Hirschfeld-Warneken, Vera C.; Neubauer, Stefanie; Rechenmacher, Florian; Medda, Rebecca; Kessler, Horst; Geiger, Benjamin; Spatz, Joachim P.; Cavalcanti-Adam, Elisabetta A. (Cell adhesion & migration, 2016)
Coordination of the specific functions of α5β1 and αvβ3 integrins is crucial for the precise regulation of cell adhesion, spreading and migration, yet the contribution of differential integrin-specific crosstalk to these processes remains unclear. To determine the specific functions of αvβ3 and α5β1 integrins, we used nanoarrays of gold particles presenting immobilized, integrin-selective peptidomimetic ligands.
Gesehen am 13.05.2020